Assessment of water quality variations due to operation of wastewater treatment plant in Ca Mau city - Ngo, Tra Mai; Thi Thanh Hang, Phan (Vietnam Journal of Marine Science and Technology, 2022)
The wastewater treatment plant (WWTP) in Ca Mau city, which is being planned for construction, will be responsible for treating domestic wastewater with a capacity of 8,000 m3/day. After being treated by the physic-biological method, the plant’s wastewater will be discharged into the Thong Nhat canal and the Tac Thu river. As a result, this article applies the MIKE21 model to calculate the range, the distance, and the concentration of typical pollutants for domestic wastewater, including TSS, BOD5, NH4+, and total Coliforms in the dry season, to provide evidence for water resource management following the plant’s construction. Two scenarios were established; in scenario 1 (S1), the WWTP is being operated inefficiently, and the wastewater has not been treated up to standards. Maximum calculation in case the processing performance = 0; in scenario 2 (S2), the WWTP is being operated efficiently. The concentration of 4 components in wastewater is lower than the critical value of QCVN 14:2008/BTNMT (column B, K = 1). The results show that the waste source will highly affect the water in the Thong Nhat canal both downstream and upstream due to the irregular semi-diurnal tide regime in case of the plant experiences problems (S1). In the case of the stable operation plant (S2), the pollutant concentrations at all positions will be lower than the critical value of QCVN 08-MT:2015/BTNMT (column B1) except for the TSS. Concentration variation is evident over time and distance: after about 1 hour and about 1 km from the source, the concentration of pollutants reaches the maximum value, then gradually decreases and ends at about 4 km after 7 hours.